Change patterns and dominant factors of drought in Baoshan City during 2010–2024 - Lin, Yueping; Zhao, Huihui; Liu, Honghua; Zhao, Lijuan; Li, Haiping; Hu, Zhiming; Zhang, Runze (Frontiers in Environmental Science, 2025)
Against the backdrop of global climate change and intensified human activities, drought conditions in Baoshan City, Yunnan Province, have undergone significant transformations. There is a pressing need to systematically elucidate the long-term spatio-temporal dynamics of drought intensity and its spatial distribution patterns in this region. This study employed monthly MODIS data (MOD13A2 and MOD11A2) from 2010 to 2024 to construct Normalized Difference Vegetation Index (NDVI) and Land Surface Temperature (LST) datasets. The Temperature Vegetation Dryness Index (TVDI) was subsequently retrieved. A comprehensive analysis integrating time-series analysis, centroid analysis, and the geographical detector method was conducted to investigate the spatio-temporal evolution characteristics of drought and its driving factors. (1) Drought exhibited significant spatial heterogeneity, with moderate and severe drought being the predominant types, collectively accounting for 81.45% of the study area. (2) The interannual TVDI showed a slight upward trend (slope = 0.0004 a-1), while the intra-annual variation followed a “high in winter and spring, low in summer and autumn” pattern. The mean winter TVDI (0.9) was approximately 1.5 times that of autumn (0.58). (3) The centroid of drought generally migrated northwestward. The longest migration distance (1.28 km) occurred from the period 2013–2015 to 2016–2018. (4) Elevation was the persistently dominant factor (q-value range: 0.648–0.721). However, the influence of human activity factors showed stage-specific enhancement, with the interaction between GDP and elevation reaching a q-value of 0.753 in 2015. (5) Transition characteristics of drought severity levels differed markedly between periods. During 2010–2017, drought primarily transitioned towards severe and mild drought (covering 8.59% of the total area), whereas during 2017–2024, mild drought areas shifted predominantly towards moderate drought (covering 6.59%). The findings of this study can provide crucial scientific evidence and decision-making support for drought prevention, control, and the formulation of regional adaptation strategies in Baoshan City.